A mixed methods study on evaluating the performance of a multi-strategy national health program to reduce maternal and child health disparities in Haryana, India - Madhu Gupta; Hans Bosma; Federica Angeli; Manmeet Kaur; Venkatesan Chakrapani; Monica Rana; Onno C.P. van Schayck (BMC, 2017)
Abstract Background A multi pronged community based strategy, known as National Rural Health Mission (NRHM), was implemented from 2005-06 to 2012-13 in India to curtail maternal and child health (MCH) disparities between poor and rich, rural and urban areas, and boys and girls,. This study aimed to determine the degree to which MCH plans of NRHM implemented, and resulted in improving the MCH outcomes and reducing the inequalities. Methods An explanatory sequential mixed methods study was conducted, first to assess the degree of implementation of MCH plans by estimating the budget utilization rates of each MCH plan, and the effectiveness of these plans by comparing demographic health surveys data conducted post (2012-13), during (2007-08) and pre- (2002-04) NRHM implementation period, in the quantitative study. Then, perceptions and beliefs of stakeholders regarding extent and effectiveness of NRHM in Haryana were explored in the qualitative study during 2013. A logistic regression analysis was done for quantitative data, and inductive applied thematic analysis for qualitative data. The findings of the quantitative and qualitative parts of study were mixed at the interpretation level. Results The MCH plans, like free ambulance service, availability of free drugs and logistics, accredited social health activists were fully implemented according to the budget spent on implementing these activities in Haryana. This was also validated by qualitative study. Availability of free medicines and treatment in the public health facilities had benefitted the poor patients the most. Accredited Social Health Activists scheme was also the most appreciated scheme that had increased the institutional delivery rates. There was acute shortage of human resources in-spite of full utilization of funds allocated for this plan. The results of the qualitative study validated the findings of quantitative study of significant (p < 0.05) improvement in MCH indicators and reduction in MCH disparities between higher and lower socioeconomic groups, and rural and urban areas. Conclusions MCH plans of NRHM might have succeeded in improving the MCH outcomes and reducing the geographical and socioeconomic MCH inequalities by successfully implementing the schemes like accredited social health activists, free ambulance services, free treatment and medicines in hospitals for the poor and in rural areas.